Utilization of Outseal PLC Microcontroller Trainer Learning Media Assisted by Mobile Applications - Satrinawati, Satrinawati; Irfan, Dedy; Mubai, Akrimullah (Universitas Negeri Padang, 2023)
The use of trainer media requires a fairly high cost. this gives a burden to students if it is required to be owned. We propose a solution by using mobile learning media as a place for students to learn the outseal Programmable Logic Controller (PLC) microcontroller trainer. Therefore, the purpose of this study is to examine the practicality, and effectiveness of the learning media for the PLC outseal microcontroller trainer assisted by mobile applications. This research was conducted on Microprocessor Microcontroller learning in Industrial Electronics Engineering department of SMK Negeri 3 Batam, Indonesia. This research was conducted using a one group pretest posttest design with quantitative and primary data types. Data was obtained using questionnaires and test instruments which were then calculated using percentages for the practicality test and Gain Score for the effectiveness test. The results of this study obtained the results that the Outseal PLC Microcontroller Trainer media is very practical with a percentage of 92.27% by teachers and 90.35% by students. The effectiveness of using this media has an impact on increasing 71% for cognitive, 72% for affective, and 78% for psychomotor students. This concludes that the learning media developed is ready to be used on a wider scale. In addition, the use of this media provides effectiveness in learning at a low cost and easily.